Tuned mass system to improve the seismic response of the Apenkai model annex - Jarro, Gabriela Araceli Hilario (2024)
or many years in Peru, the oldest essential buildings such as educational centers are not restored. Some of them have irregularly shaped pavilions. This study was carried out to obtain information on the behavior of the Apenkai model pavilions in the face of strong earthquakes, since in Peru there has been a seismic silence for 45 years. Therefore, it is necessary to evaluate the buildings in detail through one of the samples in Etabs to be able to estimate the possible failures that could occur due to irregularities. Subsequently, we obtain a passive control system that allows the structure to withstand intense movements, greater than 8.5 on the Richter scale, without affecting its architecture. For this reason, the present research study proposes a tuned mass system (TMD) in a unified or distributed way. When analyzing, the drift of the building in both directions decreases to less than 0.07% and 0.05% to make the structure behave more ductile. In addition, we must comply with the requirements of current Peruvian regulations without affecting the construction.